Students’ Perception and Motivation toward Online Learning at English Language Education in Pekanbaru - Fadilah Asmah; Andi Idayani (ELT-Lectura, 2022)
During Covid-19, the process of teaching and learning in school and university changed from offline learning into online learning. This research aims to know the students' perception and motivation towards online learning in the sixth semester of English Language Education of FKIP UIR. This research used the descriptive qualitative method.The sample was 33 of class 6A at English Language Education of FKIP UIR. Sampling was done by used Purposive sampling. The instrument of the research is questionnaires and interviews. To collect the data, the researcher used Google Form and Google Meet. The total of questions given to respondents was 48 statements using the Likert Scale. Meanwhile, the interview used open-ended questions consist of 9 questions. This study found that students have a positive perception on online learning. In infrastructure facilities, it is already available of mobile devices and internet connections. In technology, students can maximize the use of the technology. Meanwhile, student interaction with teachers and students is still lacking, so offline learning is necessary. Then, the researcher found that students have high motivation. Students' attention gets the highest percentage of 57.6%, students in building curiosity, interactive and exciting learning. In relevance, students feel that online learning is suitable to be applied in the pandemic conditions. In addition, in students' confidence, most of students are motivated to study outside the class that increases their knowledge. The last, in students' satisfaction, 48,5% of students agree that they satisfied with the implementation of online learning at the sixth semester of English Language of Education.